Pervasiveness in a competitive multi-operator environment the daidalos project. - Aguilar, Rui L. (IEEE Communications magazine)
This article briefly describes the EU-funded Daidalos project, which designs and develops a communications infrastructure for next-generation networks to enable personalized, context-aware, composite services to mobile users. The fundamental concepts rely on federation of operators who create a pervasive environment for service provisioning, on integrated mobility, security, virtual identity for users, and resource management. The project validates concepts by means of specification, implementation, and integration in a large research testbed.